PENGARUH MODEL PEMBELAJARAN QUANTUM THINKER TERHADAP KEMAMPUAN MEMBACA EKSTENSIF SISWA KELAS VIII SMP NEGERI 17 MEDAN TAHUN PEMBELAJARAN 2012/2013 - ESTER Z. PARDEDE (Basastra, 2013)
This study aims to determine the effect of Thinker Quantum Learning Model for Extensive Reading Literacy Grade VIII Junior High School 17 Year Learning Field 2012/2013. Samples were taken with controlling. From the controlling,  we get 75 people the first, then 60 people chosen at random, which is then divided into two groups: the experimental group and the control group. The method used in this study is an experimental method with a model of post-test only design group by giving two different treatment for the two groups. Data collection used is an objective test in the form of multiple choice. A total of 20 items were tested about the validity, reliability, difficulty index, and distinguishing power. Based on calculations of data, the average values ​​obtained experimental group 77.67, and the control group 63.0. Thus it can be said that the ability of the experimental group is higher than the control group in reading extensively. Hypothesis testing research done by the test "t". Based on a hypothesis test obtained t hitung price = 7.7814. ttable value at 5% significance level with df (n1 + n2 - 2) = 30 +30 -2 = 58, is 2.00. Therefore thitung greater than Ttable, or 7.7814> 2.00, then the nil hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Thus, Quantum Thinker learning model is better than conventional learning model in improving the ability of students to read extensively accepted. Keywords: Learning Model of Quantum Thinker , Extensive Reading